2015
DOI: 10.18203/2320-1770.ijrcog20150422
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subclinical hypothyroidism in North-Indian pregnant women

Abstract: INTRODUCTIONSubclinical hypothyroidism (SCH) in pregnancy is defined by a serum thyroid-stimulating hormone (TSH) concentration higher than the upper limit of the pregnancy related reference range associated with a normal serum thyroxine [T 4; either total (TT 4) or free (FT 4 )] concentration.The prevalence of hypothyroidism during pregnancy is estimated to be 0.3-0.5% for overt hypothyroidism (OH) and 2-3% for subclinical hypothyroidism (SCH).1 There are few reports of prevalence of hypothyroidism during pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Prevalence was high in age group of 21 -25 years (48.6%) than 26 -30 years' age group (37.5%), and all the study subjects belonged to either poor or lower middle socio-economic status and mean maternal age was 25.4 years. [12] Study conducted by Singh Alpana et al showed that most of the cases were primigravidae; however, there was no statistically significant association between gravidity and thyroid dysfunction. [11] A study conducted by Nirmala C et al showed high prevalence of hypothyroidism in primigravidae (57.7%) and age group <30 years (71.8%) and majority of them belonged to middle class status (57.7%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Prevalence was high in age group of 21 -25 years (48.6%) than 26 -30 years' age group (37.5%), and all the study subjects belonged to either poor or lower middle socio-economic status and mean maternal age was 25.4 years. [12] Study conducted by Singh Alpana et al showed that most of the cases were primigravidae; however, there was no statistically significant association between gravidity and thyroid dysfunction. [11] A study conducted by Nirmala C et al showed high prevalence of hypothyroidism in primigravidae (57.7%) and age group <30 years (71.8%) and majority of them belonged to middle class status (57.7%).…”
Section: Discussionmentioning
confidence: 96%
“…Sci. 2018;7 (12):1520-1523, DOI: 10.14260/jemds/2018/344 BACKGROUND Thyroid dysfunction is a common occurrence in pregnancy and the second most common cause of endocrine dysfunction in the pregnancy after diabetes. Thyroid dysfunctions in pregnancy may be overlooked and underdiagnosed, because of very non-specific and the physiological hypermetabolic state of normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists recently published data on this aspect of thyroidology. [ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 ] It must be noted that there is a wide heterogeneity in results, probably due to differing TSH cut offs for diagnosis. Some studies with uncertain or unreliable methodology have not been included in the table.…”
Section: Discussion and C Onclusionmentioning
confidence: 99%